ANALISIS CADANGAN KARBON PADA TANAMAN REKLAMASI LAHAN BEKAS PERTAMBANGAN BATUBARA DI PT. BORNEO INDOBARA - Muhammad Syamsudin Noor; Hafizianoor Hafizianoor; Suyanto Suyanto (Lambung Mangkurat University-Indonesia, 2020)
The purpose of this study is to analyze carbon stocks on reclamation area of post coal mining in Borneo Indobara Ltd. Carbon reserves referred to in this study are composed of trees, poles, saplings, litter and soil. Measurements of carbon stocks were carried out in the reclamation area of OPD WDL which is plant of 2013 and 2015. Samples were taken as many as 5 plots with a size of 20 m × 20 m in each planting year so that the total plot area in each planting year is 0.2 ha. Determination of sample points using the stratified purposive sampling method, the determination of sample points is assisted by the image of the drone by considering areas that have good and not good growth. The results showed that carbon stock per hectare in the reclamation area in 2013 was 71.84 tons or 2,155.24 tons with a total area of 30 ha, while carbon stock per hectare in the reclamation area in 2015 was 70.20 tons or 1,544.45 tons with a total area of 22 ha.